Public Capital and Growth - Arslanalp, Serkan (IMF Working Papers; Working Paper ;, 2010)
This paper estimates the impact of public capital on economic growth for forty-eight OECD and non-OECD countries during 1960 - 2001. Using the production function and its extensions, it finds a positive - but concave - elasticity of output with respect to public capital, which is robust to changes in time intervals and varying depreciation rates. Furthermore, in non-OECD countries the growth impact of public capital is higher once longer time intervals are considered.